Treatment of chronic dry eye: focus on cyclosporine - George D Kymionis (Dove Medical Press, 2008)
George D Kymionis, Dimitrios I Bouzoukis, Vassilios F Diakonis, Charalambos SiganosDepartment of Ophthalmology, Vardinoyannion Eye Institute of Crete, University of Crete, GreeceAbstract: To review the current treatment of chronic dry eye syndrome, focusing on cyclosporine A (CsA), a systematic literature search was performed using PubMed databases in two steps. The first step was oriented to articles published for dry eye. The second step was focused on the use of CsA in dry eye. A manual literature search was also undertaken based on citations in the published articles. The knowledge on the pathogenesis of dry eye syndrome has changed dramatically during the last few years. Inflammation and the interruption of the inflammatory cascade seem to be the main focus of the ophthalmologic community in the treatment of dry eye, giving the anti-inflammatory therapy a new critical role. The infiltration of T-cells in the conjuctiva tissue and the presence of cytokines and proteasis in the tear fluid were the main reason introducing the use of immunomodulator agents such as corticosteroids, cyclosporine, and doxycicline in order to treat dry eye syndrome. CsA emulsion is approved by the FDA for the treatment of dry eye, while clinical trials of this agent have demonstrated efficacy and safety of CsA. CsA seems to be a promising treatment against dry eye disease. New agents focused on the inflammatory pathogenesis of this syndrome in combination with CsA may be the future in the quest of treating dry eye. More studies are needed to determine the efficacy, safety, timing, and relative cost/effect of CsA.Keywords: dry eye, cyclosporine A, inflammation, immunomodulator agents